The Effect of FDR, OER And ROA on The Performance of Islamic Banks Listed on The Indonesia Stock Excange 2014-2024 - Adi Prawira; Nasfi Nasfi (Imara: Jurnal Riset Ekonomi Islam, 2026)
Background. The Islamic banking industry in Indonesia has undergone significant structural transformation, particularly following the merger forming Bank Syariah Indonesia in 2021. Post-merger, BSI’s profitability from 2022 to 2024 was driven by operational cost efficiency and growth in productive financing, with the FDR and OER (BOPO) ratios contributing to its profitability during that period.. Purpose. The purpose of this study is to analyze the influence of FDR, OER, and ROA on the performance of Islamic banks listed on the Indonesia Stock Exchange (IDX) for the 2014–2024 period. Method. This quantitative research method employs a multiple linear regression approach. Secondary data from the banks’ annual financial reports were selected using a purposive sampling technique, resulting in 34 observations and a sample consisting of four banks listed on the Indonesia Stock Exchange. The multiple linear regression analysis was conducted using SPSS Statistics 27 software. Results. The partial results of the study indicate that the FDR and OER variables have no significant effect on Bank Performance, the ROA variable has a positive and significant effect on Bank Performance. Simultaneously, the three independent variables have a significant effect on Bank Performance, with an F test significance value of 0.000 (<0.05). The Adjusted R Square (R²) value of 0.814 indicates that 81.4% of the variation in Bank Performance changes can be explained by the FDR, OER, and ROA variables, while the remaining 18.6% is explained by other factors outside the research model Conclusion. First, the FDR variable has no significant effect on financial performance. Second, the OER variable also has no significant effect on financial performance. Third, the ROA variable has a positive effect on financial performance. Fourth, simultaneously, FDR, OER, and ROA significantly influence financial performance, so the regression model used is considered adequate to explain the relationship between these variables